(untitled) (Progressive Agriculture, 2016)
This study was conducted in order to investigate the effect of scion defoliation period and methods of grafting on the success and survivability of mango (var. Amrapali) at Bangladesh Agricultural University Germplasm Centre (BAU-GPC) of Fruit Tree Improvement Program (FTIP) of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh. The experiment consisted of four scion defoliation periods, viz., defoliation before 9, 6, 3 days of grafting and defoliation on the day of grafting and two grafting methods namely cleft grafting and whip grafting. The study was laid out in randomized complete block design with three replications. The results revealed that scions defoliated 9 days before grafting showed the highest success (91.59%) and survivability (88.75%) and took the lowest time for bud breaking and first leaf opening (11.10 days and 14.22 days, respectively)whereas the lowest success rate (85.82% ) and survivability (83.60%) were observed when scion defoliation was performed on the day of grafting. In respect of grafting methods, higher graft success and survivability (89.68% and 86.89%, respectively) were found in cleft method, however, this method took longer time for bud breaking (11.92 days) and first leaf opening (15.90 days). The combined influence of scion defoliation period and grafting method exhibited the best performance on graft success and survivability when cleft grafting method was used with scion defoliated 9 days before grafting operation. Therefore the results of this investigation suggested that scions defoliated 9 days before grafting operation and cleft grafting method would be better for propagation of mango, yet the performance of cleft grafting with scion defoliated 6 days before grafting was also good with the hope of getting 85% success and survivability. Progressive Agriculture 27 (3): 242-248, 2016